1997
DOI: 10.1002/(sici)1097-0142(19970315)79:6<1150::aid-cncr13>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy-induced neutropenia and fever in patients with metastatic breast carcinoma receiving salvage chemotherapy

Abstract: retrospective analysis, the authors evaluated the incidence of neutropenic fever, fever (41 episodes among 40 patients). The incidence of neutropenic fever did not Anderson Cancer Center, Houston, Texas.increase until the absolute neutrophil count (ANC) had decreased to less than 500/ mL, and then fever incidence had a linear relationship with decreasing ANC (linear trend, P õ 0.01). A source of infection was documented in 59% of the neutropenic fever episodes. The incidence of infection did not increase signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 25 publications
2
18
0
Order By: Relevance
“…We propose that all major clinical observations regarding the development of infections in neutropenic patients are consistent with our model. First, the severity and duration of the neutropenic nadir are known to be correlated with increased risk of infection (1,18). The existence of the BNC indicates that the severity and duration of the nadir directly influence the likelihood of developing a severe infection, thus explaining the observed correlation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We propose that all major clinical observations regarding the development of infections in neutropenic patients are consistent with our model. First, the severity and duration of the neutropenic nadir are known to be correlated with increased risk of infection (1,18). The existence of the BNC indicates that the severity and duration of the nadir directly influence the likelihood of developing a severe infection, thus explaining the observed correlation.…”
Section: Discussionmentioning
confidence: 99%
“…Second, at some ranges of nadir levels and nadir durations, the risk of infection greatly increases (1,18). For these near-critical ranges, there was strong interpatient variability in infection development.…”
Section: Discussionmentioning
confidence: 99%
“…Poo r perfo rm a nce statu s was d efined as WH O grade > 1; 15,24 Eastern Cooperative Oncology Group (ECOG) grade > 1; 18,[25][26][27] Zubrod's scale grade > 1; 28 or as grade > 1 using an undefined scale. 16 Four studies reported that poor performance status (PS> 1) was a significant risk factor (P= 0.002 to P< 0.000), 16,[26][27][28] while four other studies that examined performance status reported it not to be a significant risk factor. 15,18,24,25 One of these studies 24 defined neutropenia as grade 3 -4 and found performance status to be significant in univariate analysis; this factor did not remain an independent significant predictor in multivariate analysis.…”
Section: Advanced Age (Generally Defined As > 60 Years Old)mentioning
confidence: 99%
“…In particular, chemotherapy often causes neutropenia since it typically attacks cells indiscriminately regardless of whether malignant or normal. In fact, neutropenia is one the most frequent side-effects of chemotherapy (Rahman et al, 1997;Vainstein et al, 2005). Administration of recombinant forms of the growth factor G-CSF has been shown to stimulate neutrophil production and is now the standard treatment for neutropenia.…”
Section: Introductionmentioning
confidence: 99%